Molecular analysis of RAX2-regulated retinal development using human retinal organoids at a single-cell resolution - Wang, Shaojun; Sun, Yi; Na, Jie; Huang, Yue; Liu, Guang (Frontiers in Cell and Developmental Biology, 2025)
Human embryonic stem cells (hESC)-derived retinal organoids are sophisticated in vitro systems for dissecting the complex dynamics of human retinal development. The formation of the human retina is a precisely organized process that depends on the regulated differentiation of retinal progenitor cells; however, many of the basic mechanisms remain to be explored. Here, using hESC-derived retinal organoids, we elucidated the temporal contribution of RAX2 to retinal development, with an emphasis on photoreceptor cells (PC) formation. The results were corroborated using human fetal retinal tissue at various gestational ages. Using CRISPR/Cas9-mediated gene knockout, we delineated the essential role of RAX2 in modulating PC specifications. RAX2 deficiency significantly altered the expression of PAX6 and SOX2, two essential regulators of retinogenesis. Our results suggested that RAX2 is significant in retinal development, underpinning its potential as a therapeutic target in related retinal disorders.